Analysis Performance of Coconut Coir as Natural Geotextiles - Bawadi, Nor Faizah; Che Basri, Nurfarah Syahirah; Mansor, Ahmad Faizal; A Hamid, Siti Hasmah; Md Nujid, Masyitah; Mohammad Zaki, Mohd Faiz; Ahmad, Muhammad Munsif; Md Ghazaly, Zuhayr (International Journal of Integrated Engineering, 2025)
Agricultural waste offers significant potential for natural geotextiles due to its eco-friendliness and mechanical properties. Coconut coir, among fibres like jute, sisal, and kenaf, stands out for its suitability in geotechnical applications. This research evaluates the effectiveness of coir mats in improving clayey soil properties, focusing on chemical composition, physical characteristics, and geotechnical performance. Laboratory experiments, including specific gravity, Atterberg limits, unconfined compressive strength (UCS) and direct shear tests, were conducted to analyse the treated soil. The clay soil, classified as organic (A-7-5) based on AASHTO standards, had a specific gravity of 2.09 and a plasticity index of 30. Results showed significant improvements in mechanical properties with coir reinforcement. Single-layer coir mats enhanced the UCS by 15%, while double-layer mats achieved a 20% increase. Direct shear tests revealed higher cohesion and internal friction angle, indicating better shear strength and stability. These findings confirm coconut coir as an effective, sustainable geotextile for enhancing clay soil stability, strength, and shear resistance. This study highlights its potential in eco-friendly geotechnical applications, supporting sustainable construction and promoting the use of biodegradable materials in soil stabilisation projects.